Assessing the impact of workers attitude to productivity in some selected organizations in Ejisu Juaben Municipality - Amofa, Abena Dwomo (2015)
A thesis submitted to the Department of Managerial Science, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Business Administration (HRM Option), 2013